INFLUENCE OF ’MAUDY.AYUNDA’ AS CELEBRITY ENDORSER, BRAND IMAGE, AND BRAND ORIGIN ON PURCHASE INTENTION OF POND’S - Elita Herdianti, Siti; Muttaqien, Dadan Darmawan; Arief Surya Lesmana; Salwa Ghina Zahira (Cirebon International Conference on Education and Economics Proceeding, 2024)
The rapid development in the business world has spurred intense competition across various sectors, including the skincare industry. Pond’s, a facial moisturizer brand under the Unilever umbrella, has witnessed consecutive declines in sales from 2019 to 2023. This indicates a waning consumer interest in Pond’s facial moisturizer. This research seeks to analyze the effect of the celebrity endorser "Maudy Ayunda," along with brand image and brand origin, on consumer purchase intention for Pond’s facial moisturizer. The study adopts a quantitative approach using a survey method, employing both descriptive and verification techniques. A sample of 100 respondents filled out the questionnaire on an interval scale (1-10). Data analysis includes instrument validation (validity and reliability tests), descriptive analysis, classical assumption tests (normality, multicollinearity, heteroskedasticity tests), multiple linear regression analysis, determination coefficient analysis, and hypothesis testing (F-test and t-test). The findings indicate that: (1) Celebrity Endorser "Maudy Ayunda," Brand Image, and Brand Origin significantly influence consumer purchase intention towards Pond’s products among consumers in Kuningan Regency. Alterations in consumer purchase intention can be detected through the variables of celebrity endorsement., brand image, and brand origin. (2) Celebrity Endorser presence has a significant positive impact on consumer purchase intention. As the popularity of a celebrity endorser increases, it directly contributes to higher purchase intention for the endorsed products. (3) Brand Image has a positive impact on purchase intention. This suggests that an enhanced brand image leads to increased consumer purchase intention towards the product. (4) Brand Origin positively affects purchase intention. When the reputation of a brand's origin improves, it influences increased purchase intention towards the product.